Doses and sources of nitrogen fertilizer and their effects on soil chemical properties and forage yield of Brachiaria brizantha cv. Xaraes - Heinrichs, Reges [UNESP]; Soares Filho, Ceclio Viega [UNESP]; Crociolli, Carlos Alberto [UNESP]; Monteiro de Figueiredo, Paulo Alexandre [UNESP]; Fruchi, Viviane Murer [UNESP]; Kodel, Francisco Juliano [UNESP]; Rodrigues, Tiago Arriero [UNESP] (Universidade Estadual de Londrina (UEL), 2012)
Forage plants, particularly the Brachiaria genus, are the main source of nutrients for cattle and are at times the only feed offered. The concentration of elements in the plant is related to the soil, fertilization, climate, season, variety, and cultural practices. An experiment on dystrophic Red-Yellow Latosol soil in Aracatuba, São Paulo was performed to evaluate the effects of the doses and sources of nitrogen fertilizers on the chemical properties of the soil and the dry matter yield of the grass Brachiaria brizantha cv. Xaraes. A randomized block design was employed involving three replicates in a 3 x 3 factorial, with three doses (100, 200 and 400 kg ha(-1) year(-1)) and three sources (Ajifer (R) L40, ammonium sulfate and urea) of nitrogen and a control treatment without nitrogen (zero). The greatest effects on the chemical properties of the soil as a function of nitrogen fertilization in the Xaraes grass were observed in the topsoil. The use of Ajifer (R) L40 and ammonium sulfate as sources of nitrogen had similar effects, with an increase in the sulfur content and a reduction in the soil pH at the superficial layer. The use of the fertilizers Ajifer (R) L40, ammonium sulfate and urea did not affect the micronutrient contents, except for Fe and Mn, and did not alter the sodium concentration or electrical conductivity of the soil. The dry matter yield of Xaraes grass was similar for all three nitrogen sources.
Keywords: Ajifer (R) L40; forage plant; plant nutrition; pasture; ammonium sulfate; urea